ASPECTS-based selection for late endovascular treatment: a retrospective two-site cohort study. Issue 4 (April 2022) - Nannoni, Stefania; Kaesmacher, Johannes; Ricciardi, Federico; Strambo, Davide; Dunet, Vincent; Hajdu, Steven; Saliou, Guillaume; Mordasini, Pasquale; Hakim, Arsany; Arnold, Marcel; Gralla, Jan; Fischer, Urs; et al.
Introduction: The DAWN trial demonstrated the effectiveness of late endovascular treatment in acute ischemic stroke patients selected on the basis of a clinical-core mismatch. We explored in a real-world sample of endovascular treatment patients if a clinical-ASPECTS (Alberta Stroke Program Early CT Score) mismatch was associated with an outcome benefit after late endovascular treatment. Methods: We retrospectively analyzed all consecutive acute ischemic stroke patients admitted 6–24 h after last proof of good health in two stroke centers, with initial National Institutes of Health Stroke Scale (NIHSS) ≥10 and an internal carotid artery or M1 occlusion. We defined clinical-ASPECTS mismatch as NIHSS ≥ 10 and ASPECTS ≥ 7, or NIHSS ≥ 20 and ASPECTS ≥ 5. We assessed the interaction between the presence of the clinical-ASPECTS mismatch and late endovascular treatment using ordinal shift analysis of the three-month modified Rankin Scale and adjusting for multiple confounders. Results: The included 337 patients had a median age of 73 years (IQR = 61–82), admission NIHSS of 18 (15–22), and baseline ASPECTS of 7 (5–9). Out of 196 (58.2%) patients showing clinical-ASPECTS mismatch, 146 (74.5%) underwent late endovascular treatment. Among 141 (41.8%) mismatch negative patients, late endovascular treatment was performed in 72 (51.1%) patients. In the adjusted analysis, late endovascular treatment was significantly associated with a better outcome in the presence of clinical-ASPECTS mismatch (adjusted odd ratio, aOR = 2.83; 95% confidence interval, CI: 1.48–5.58) but not in its absence (aOR = 1.32; 95%CI: 0.61–2.84). The p -value for the interaction term between clinical-ASPECTS mismatch and late endovascular treatment was 0.073. Conclusions: In our retrospective two-site analysis, late endovascular treatment seemed effective in the presence of a clinical-ASPECTS mismatch, but not in its absence. If confirmed in randomized trials, this finding could support the use of an ASPECTS-based selection for late endovascular treatment decisions, obviating the need for advanced imaging.